Nickel silicide formation on Si(100) and Poly-Si with a presilicide N2 + implantation - Mangelinck, D. (2013)
The key feature of this study is to incorporate N2 + implant prior to Ni sputtering on the poly-Si gate and source/drain regions. The results show that the incorporation of the presilicide N2 + implant is able to suppress agglomeration in the Ni silicide films up to 900°C and enhance the phase stability of NiSi on Si(100) up to 750°C. Stable and low sheet resistance was achieved on the silicided undoped poly-Si up to 700°C due to reduced layer inversion, which is driven by grain boundary energy and the surface energy of the poly-Si.